Multimodalities Element In The Cartoon Work Through Linguistic Modes And Visual Modes - Nur Izzati binti Abdullah; Anida Sarudin; Zulkifli Osman; Husna Faredza Mohamed; Mazura Mastura Muhammad; Marlini Idris (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2020)
In cartoons, meanings and messages are generated either through two semiotic modes that are verbal and visual or solely through visual modes. Interaction between language and cartoon images is often regarded as a straightforward and easy-to-process way to convey a message. This study aims to show that the meaning and cartoon messages are not always easy to understand, therefore readers should observe the language and visual information of each cartoon. This study is aimed at identifying the linguistic modes and the visual modes in the cartoons to convey the meaning and the explicit message or implied message. For this purpose, two theories are adopted; Systemic Functional Linguistics Theory by Halliday (1994) to analyze linguistic modes and multimodal approach by Kress and Van Leeuwen (1996, 2006) to analyze visual modes or images in cartoons. The research data was obtained from Usik-Usik cartoon book (Cynical Collection of the World of Education). The findings indicate that language text is a linguistic modes that acts as an effective multimodal element and complement the visual modes in the cartoon work. Furthermore, the findings of the study also show that the role of linguistic modes is to provide the context in the cartoon work as additional information so that the reader can understand the messages to be communicated more clearly.